Roll control problem for the long-range maneuverable warhead. Issue 5 (26th August 2014) - Wei, Peng-xin; Gao, Chang-sheng; Jing, Wu-xing
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a combination bank-to-turn control mode with the single moving mass and reaction jet and design the roll control law for the long-range reentry maneuverable warhead. Design/methodology/approach – Based on the dynamics model of this new control mode, the control model of roll channel is converted into a perturbed double-integrator system. The on-off optimal feedback control law is designed on the phase plane formed by Euler angle error and angular velocity error. To weaken the "on-off chattering" that is generated near the origin of the phase-plane and effectively reduce the jet fuel consumption for stability control, an on-off control outer ring and an inner ring are introduced into the phase plane. Findings – This control mode can not only avoid the aerodynamic rudder ablation to improve the efficiency of attitude control, but also reduce the fuel consumption of jet control by using moving mass control. The simulation results indicate that the designed control law can meet the speediness and robustness requirements of the long-range maneuverable warhead controlled by the single moving mass and reaction jet. This measure can also eliminate the on-off chattering effectively. Practical implications – The new control mode solves some engineering problems of long-range reentry maneuverable warhead controlled by only one actuator. The control mode has a promising prospect in engineering practice. Originality/value – The paper provides a new control mode and a combination control strategy, and designs an effective control law.